Documentation of Palu'e; Storytelling and folklore - Danerek, Stefan (Wacana, Journal of the Humanities of Indonesia, 2017)
This paper presents Palu'e storytelling on the basis of the on-going work with the Palu'e audio collection, created in the context of language/oral traditions documentation. The main aim is to show that the collection is a research resource for the humanities by discussing and comparing items which are referenced and accessible in the Kaipuleohone Ethnographic Archive. While the contents of the collection are showcased for this specific presentation, the intention is directed towards the body of digital humanities collections. The problems of what genres should be included, definitions, method of analysis, are discussed and put to the test. Recordings initially focused on oral literature, but expanded to include personal narratives with content related to culture and tradition. The cross-referencing between genres and items demonstrates the benefits of a comparative methodology, and suggests ways of using the collection.